The Influence of Movie Spoilers on Social Media Instagram Towards the Decision to Watch South Korean Drama Shows: Study on SMA Negeri 42 Jakarta - Arniza Devita Putri; Dalilah Adani (Jurnal Mantik, 2021)
This study aims to determine the effect of spoiler impressions on social media Instagram on the decision to watch South Korean drama (K-drama). Korean drama is one form of the entertainment industry that is in great demand by generation Z around the world, including Indonesia. The Korean wave phenomenon is spread massively through social media. The information about the latest K-drama shows is disseminated through spoiler on Instagram. The uses and gratifications theory is the main theory used in this study. This study using a quantitative approach to a casualty with a survey method. The total population of 888 students and a sample of 276 students were obtained based on the Slovin formula with a stratified random sampling technique. The data were collected by questionnaire with a Likert scale. The data were analyzed using the SPSS-24 version and simple linear regression analysis. The result of this study indicates the influence effect of spoiler on Instagram on the decision to watch K-dramas significantly.